Academic Senate Minutes 2005-10-27 - Academic Senate:::::::::
Chair's Report. Approval of Agenda. Approval of Minutes of 10/13/05. B.S in Biochemistry approved. Information item: Senate Self Study. Annual report from Academic Council on International Program representative Christine Renaudin. Periodic Review of Administrators Policy approved. Program Review Protocol postponed. Course Outline Policy First Reading. Resolution endorsing the Statewide Senate Resolution: Re-Affirmation of Prior Actions and Statements on Merit Pay approved. Provost's Report. Good of the Order.